Analisis Pengalaman Pengguna Light dan Dark Mode Pada Facebook dan Tokopedia Menggunakan Within-Subject Design - Muhammad Farhan; Chanifah Indah Ratnasari (Journal of Information System Research (JOSH), 2026)
The use of light mode and dark mode in mobile applications is becoming increasingly common; however, their effects on user experience across different application contexts still need to be empirically examined. This study aims to analyze differences in user experience between light mode and dark mode in Facebook and Tokopedia. The study employed a quantitative approach using a within-subject design (repeated measures design) involving 25 respondents. Measurements were conducted using Time on Task, Error Rate, the User Experience Questionnaire (UEQ), and user preference. The results showed that Facebook had no significant difference in Time on Task, whereas Tokopedia showed significant differences in T1 (p = 0.024) and T3 (p = 0.047). For Error Rate, significant differences were found in Facebook T1 (p = 0.046) as well as Tokopedia T2 (p = 0.020) and T3 (p = 0.019). The UEQ results indicated that both modes were in the positive category without statistically significant differences. These findings suggest that the influence of display mode is more evident in specific task performance metrics than in overall user experience perception, indicating that its effects are contextual. This study contributes by providing a comprehensive evaluation that combines objective and subjective metrics to compare light mode and dark mode across two different application contexts.